INDENTIFYING PRAGMATIC FAILURES IN DIALOGUE SCRIPTS OF EFL LEARNERS - Amna, Shally (Journal Of Language Education and Development (JLed), 2018)
Most of the EFL learners consciously or unconsciously speak English using the same way they communicate their native languages which have different patterns and cultural backgrounds. In writing English dialogue scripts, most students in West Sumatera province transfer their mother languages to national language first and then to English language. As a result, beyond many spelling and syntactic errors found in the scripts, pragmatic failures are the most dominant issues captured. The students’ pragmatics failures are categorized into pragmalinguistic and sociopragmatic failures in accordance with Jenny Thomas (1983). This present study provides overviews of phenomenon in EFL dialogue scripts made by students of UPI YPTK Padang. It investigated students from 6 classes who have learned basic English in the previous semester. The students are asked to make a simple dialogue in groups with certain chosen topics and are allowed to use dictionary if necessary. The study showed that the students limitation of English language proficiency and pragmatic transfer result in pragmalinguistic failures such as failure to follow the native expressive habit, misunderstanding of words, use English with semantics and structure of students’s mother tongues, verbose verbs and that sociopragmatic failure lies in perception and expression of local pragmatic conventions.